Pandemi Covid-19: Ekonomi Dan Kemiskinan Kota Surabaya - M Fikri Amrullah; Hendra Hendra (Universitas Negeri Makassar, 2023)
The restrictions on community activities during the Covid-19 pandemic have brought nearly all aspects of community life in Surabaya City to a halt, particularly social movements within the community that directly impact economic activities. The increasing unemployment rate is one of the direct effects of the pandemic. In general, the massive impact of the spread of the Covid-19 virus on the economy will significantly affect the changes in the number of poor people in Surabaya City before and after the pandemic. The objective of this research is to identify changes in the number of poor people and the influence of the pandemic on the economic conditions of Surabaya residents. This descriptive study utilizes secondary data sourced from the Central Statistics Agency (Badan Pusat Statistik). During the pandemic, the increase in the number of poor people in Surabaya was influenced by several factors such as job restrictions, layoffs, reduced productivity due to Covid-19 infection, and others. In 2019, the number of poor people in Surabaya amounted to 4.51%, while after the Covid-19 pandemic, the number of poor people increased to 5.21% in 2021.